Changes in normal polymorphonuclear leucocyte motility after ingestion of IgG aggregates. Issue 2 (April 1984) - Goddard, D H; Kirk, A P; Brown, K A; McCarthy, D; Johnson, G D; Holborow, E J
Abstract : Changes in normal polymorphonuclear leucocyte (PMN) motility after membrane-binding and internalisation of IgG aggregates (a model of soluble immune complexes) have been studied by the micropore filter assay. The results have confirmed that IgG aggregates stimulate as well as inhibit PMN chemotaxis. These effects are dependent on the size and concentration of the IgG aggregates in solution as well as the length of time of incubation. Stimulated chemotaxis was observed in a small subset of the whole PMN population which was apparent only when cell distribution through the filters was analysed. These results indicate the need for caution when drawing conclusions about PMN function from results obtained by these assay techniques.